Effectiveness of small group cognitive behavioural therapy for anxiety and depression in Ebola treatment centre staff in Sierra Leone. (17th February 2021) - Cole, Charles L.; Waterman, Samantha; Hunter, Elaine Catherine Margaret; Bell, Vaughan; Greenberg, Neil; Rubin, G. James; Beck, Alison
Abstract: Following the 2014 Ebola outbreak, South London and Maudsley NHS Foundation Trust (SLAM) were commissioned to provide a 'culturally appropriate, effective and sustainable' intervention to address the psychological needs of the Sierra Leonean Ebola Treatment Centre (ETC) staff. The study evaluated the effectiveness of group Cognitive Behavioural Therapy (CBT) developed to treat anxiety, depression and functional impairment amongst a sample of former ETC staff in Sierra Leone. Group comparisons explored whether the effect of the intervention differed dependent on the facilitators that delivered it, as well as whether it differed between former staff of high- and low-risk ETC roles. A sample of 253 former ETC staff attended the group CBT intervention comprised of eight sessions over six weeks. Outcome measures were administered upon entry and within two weeks after the intervention. At post-intervention, anxiety, depression and functional impairment significantly reduced. Reading ability (RA) was introduced as a covariate having impacted the outcomes. The intervention effect differed by facilitators delivering the sessions but not by ETC role risk. The implications of these results are discussed. Group CBT is a promising psychological intervention for treating the anxiety, depression and functional impairment of former ETC staff in Sierra Leone. Furthermore, as part of a stepped-care approach, it may provide a model for psychological support for staff that have worked on the frontline during future epidemics.